Cartographie De La Dynamique Spatio-Temporelle Des Parcours Naturels Des Troupeaux Transhumants Dans Les Communes De Banikoara Et De Karimama Au Benin (Afrique De L’ouest) - Issiaka, Nourou Toko; Arouna, Ousséni; Imorou, Ismaïla Toko (European Scientific Journal, ESJ, 2016)
Cattle breeding in the Districts of Banikoara and Karimama is characterized by semi-nomadic and transhumance with a food system based on the exclusive use of rangelands and crop residues; in this context, the risk of degradation of these rangelands are so high. The aim of this research is to assess the physiognomy changes recorded in these rangelands from 2000 to 2013.The techniques of the remote sensing in particular the classification of the Landsat images ETM+ of 2000 and OLI-TIRS of 2013 were used. The transition matrix was produced using the Intersect function of the software ArcGIS 10.1. In the same way, the programs "PontiusMatrix22" and "Intensity Analysis02" were used to measure the intensity and the speed of land covers units changes.Thus, the surface of riparian forests and the woodlands and savannas woodlands passed respectively from 1.86 % and 12.69 % in 2000 to 1.82 % and 6 % in 2013.Tree and shrub savannas knew a progressive evolution of their surface which passed from 37.55 % in 2000 to 40.51 % in 2013. In addition, the mosaics of fields and fallow which are used as surfaces of pasture in dries season also knew an appreciable increase in their area which passed from 47.02 % in 2000 to 51.73 % in 2013. In total, there was a regression of forest formations in favor of savanna and anthropogenic formations.The highest speed changes was recorded on the level of woodlands and savannas woodlands.